Refining the definition of sustainable agriculture: An inclusive perspective from Malaysian vegetable sector - Yeong-Sheng Tey (Maejo International Journal of Science and Technology, 2012)
Skepticism about the longevity of conventional agriculture has resulted in the quest for sustainable agriculture. Like many developing countries, a homogenous definition of the term ‘sustainable agriculture’ is yet to be developed in Malaysia. To fill this gap, using an inclusive perspective, this study posits a refined definition of ‘sustainable agriculture’ for Malaysia.Cognizant of relevant past studies, which were built on rather narrow viewpoints, this study integrates qualitative insights from selected up-stream stakeholders in Malaysian vegetable sector. The structured results suggest that sustainable agriculture can be defined as the process by which anintegrative balanced agricultural system is realised through a dynamic set of practices that are (1) environmentally enhancing, (2) resource optimal, (3) economically viable, (4) socially justifiable and (5) functionally feasible over time. Though derived from Malaysia, this definition can be adapted to fit local nuances in other countries and sectoral emphases in agriculture. With these five inter-related operational attributes, which are capable of enhancement and/or modification periodically, this flexible definition can progressively provide potential direction towards academic understanding and development of agricultural sustainability.